Effect of Alternate Wetting and Drying Irrigation on the Nutritional Qualities of Milled Rice - Song, Tao; Das, Debatosh; Zhu, Fuyuan; Chen, Xiaofeng; Chen, Moxian; Yang, Feng; Zhang, Jianhua (Frontiers in Plant Science, 2021)
Alternate wetting and drying (AWD) irrigation has been widely used to save irrigation water during rice production when compared to the traditionally continuous flooding (CF). Although the influence of AWD on water saving potential and grain yield has been studied before, its detailed effect on grain nutritional quality in milled rice remains relatively unexplored. In this study, AWD could maintain grain yield as compared to CF. Thus, we undertook efforts to compare the nutritional traits of milled rice irrigated with AWD and CF regimes. A targeted metabolome assay on milled rice identified 74 differentially accumulated metabolites with 22 up- and 52 down-accumulated metabolites under AWD vs CF. Clustering of the metabolite content obtained in this assay suggested that most of the metabolites showing significant changes belonged to “lipids”, “alkaloids” and “phenolic acids”. In addition, total protein, starch, lipid and amino acids content was measured to correlate it with the differential accumulation of specific metabolites detected in metabolome. Overall, the data suggested that AWD may improve the nutritional performance of milled rice by increasing amino acids and phenolic acids and decreasing lipids and alkaloids. Our work provides a research proof for need of optimization of irrigation to optimise rice nutritional qualities.